Clinical-functional vulnerability index in older people of a family health strategy team in the central zone of Rio de Janeiro - Felipe Gonçalves Martins; Lívia Maria Santiago (Archives of Gerontology and Geriatrics Plus, 2024)
Aim: To evaluate the applicability of the Clinical-Functional Vulnerability Index (IVCF-20) in monitoring the health of older people in primary health care (PHC), estimate the prevalence of functional decline and identify associated factors. Methods: Cross-sectional descriptive study, with individuals aged 60 or over, from a PHC unit in Rio de Janeiro. The instrument included sociodemographic, health and lifestyle variables and the IVCF-20. A descriptive analysis was carried out, prevalence ratios (PR) were calculated, and Poisson multiple analysis was performed. Results: The sample consisted of 120 individuals, mean age of 72.9 years (SD= 0.75), the majority were female. According to IVCF-20, 61 (50.8 %) of the individuals were robust, 41 (34.2 %) were in potential functional decline and 18 (15.0 %) were in established functional decline. In the bivariate analysis, not performing regular physical activity (RP 2.60 CI95 % 1.21–5.57), not believing that you live a healthy life (RP 4.39 CI95 % 1.92–10.06), not being satisfied with the way you live (RP 6.74 IC95 % 2.51–18.11) and reference to chronic illness (RP 4.57 IC95 % 1.22–17.14) showed an association with functional decline. In the Poisson model, the variables age (RP 1.37 95 % CI 1.07–1.75), not believing that you live a healthy life (RP 1.54 95 % CI 1.01–2.33) and lack of satisfaction with the way you live (RP 1.75 CI95 % 1.18–2.60) remained associated. Conclusion: The study made possible to draw a profile of the older adults accompanied by a team at PHC, contributing to discussions on care proposals for the older people with a focus on preventing functional decline.